penguatan karakter religius melalui profil pelajar pancasila pada kurikulum merdeka di MI Miftahul Khoir III Purwosari - Nada, Zahrotul Qotrun; Yusuf, Wiwin Fachrudin; Yusuf, Achmad (Yayasan Rahmat Islamiyah, 2024)
The process of internalizing religious values will be able and realized in the school if there is an habituation carried out by the school community. From the habituation carried out, it is hoped that students will form a more religious character, with religious activities that are in accordance with the implementation of the independent curriculum issued by the school to form religious character. Therefore, researchers want to dig deeper regarding strengthening religious character in the independent curriculum through the Pancasila student profile on attitude development. and student behavior in the school environment. This research method uses descriptive qualitative, namely research that presents data collected in words or images. The purpose of this research is to examine and identify the implementation of the Independent Curriculum in developing students' religious character through the Pancasila student profile.